2003
DOI: 10.1093/ps/82.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese herbal polysaccharides on the immunity and growth performance of young broilers

Abstract: Two trials were conducted to study the effects of two Chinese herbal polysaccharides [achyranthan (ACH), a low-molecular-weight polysaccharide, and astragalan (APS), a high-molecular-weight polysaccaride] on the immunity and growth performance of young broilers. Trial 1 was a 28-d growth assay, in which 7-d-old broilers (n = 240) were randomly allotted to one of three dietary treatments, with eight replicate pens per treatment and ten chickens per pen. Dietary treatments included a control corn-soy-fishmeal (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 7 publications
8
73
0
2
Order By: Relevance
“…The results of the present study are in agreement with the findings of Kleessen et al (2003) who observed an increase in the relative weight of bursa of broilers in response to the consumption of Jerusalem artichoke fructans syrup (0.5%) administered via drinking water. Chen et al (2003) noted a significantly larger bursa and greater immunomodulatory effect in broilers fed diets supplemented with two Chinese herbal polysaccharides, astragalan and achyranthan.…”
Section: Lymphoid Organ Weights and Humoral Immune Responsesmentioning
confidence: 95%
“…The results of the present study are in agreement with the findings of Kleessen et al (2003) who observed an increase in the relative weight of bursa of broilers in response to the consumption of Jerusalem artichoke fructans syrup (0.5%) administered via drinking water. Chen et al (2003) noted a significantly larger bursa and greater immunomodulatory effect in broilers fed diets supplemented with two Chinese herbal polysaccharides, astragalan and achyranthan.…”
Section: Lymphoid Organ Weights and Humoral Immune Responsesmentioning
confidence: 95%
“…In some instances the presence of fructo-oligosaccharides and mananoligosaccharides, which may be produced within the GIT, has proved to be beneficial in reducing the presence of pathogenic bacteria and improving the health of the GIT. This outcome may be a result of alteration of the pH and/ or interference with the ability of micro-organisms to attach to the epithelial tissue within the GIT (Spring et al 2000;Houdijk et al 2002;Chen et al 2003;Spring, 2004).…”
Section: Bioactivity Of Plant Secondary Metabolitesmentioning
confidence: 99%
“…The spleens and bursas of Fabricius were collected and the weights were expressed as the splenic/bursal index. Blood samples were collected by cardiac puncture and subjected to assays for NO and clinical chemistry, such as aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (Chen et al, 2003).…”
Section: Methodsmentioning
confidence: 99%